Qualidade e composição mineral de pedúnculos de clones de cajueiro-anão cultivados em Alto Santo e Beberibe, CE - Almeida, Maria Lucilania Bezerra (2017)
The quality characteristics of fruits have a genetically defined amplitude, but for the expression of all their genetic potential to occur, it is necessary the influence of several factors, such as the adequate attendance of nutritional requirements, edaphoclimatic conditions and cultivar. The objective of this study was to evaluate the physical, the physical-chemical quality and the total antioxidant activity of cashew apple, as well as the nutritional composition of soil, leaves and cashew apple of clones of dwarf cashew tree, in different regions of Ceará, during two consecutive years. The experimental design was completely randomized, in a factorial scheme with repeated measures in time, applying the confounding, being three clones (CCP 09, BRS 265 and PRO 555-1) in two regions, a sertão region (Alto Santo) and the other, a coastal area (Beberibe), with four replications, evaluated in the years of 2013 and 2014. In the post-harvest laboratory, the fruits were evaluated for total mass (g), nut and cashew apple mass (g), length, diameter of the apical and basal cashew apple (mm), firmness (N), pH, soluble solids (SS, °Brix), titratable acidity (TA, % malic acid), SS/TA, soluble sugars (SS, % glucose), vitamin C (mg 100 g-1), total extractable polyphenols (TEP, mg 100 g-1), cinnamic acid (CA, mg L-1), transcinnamoyl glycoside (TG, mg L-1) and total antioxidant activity (TAA, μmol Trolox g-1). The N, P, K, Ca, Mg, Na, Fe, Zn, Mn and B on the soil, cashew apple and leaves were also analyzed. It was observed that the CCP 09 showed a higher physical-chemical quality and TAA than the others, responding in a positive way to the variations of the edaphoclimatic conditions. Regarding the physical characteristics, CCP 09 was the only one that presented similar behavior in both regions. The others differed, presenting superior physical quality for the coastal region. In the sertão region, the best adapted was CCP 09; and on the coast, it was the clone PRO 555-1. The highest mean values of SS, TA, SS, vitamin C, TG, TEP and TAA were obtained in the sertão region. The TAA attributed to the cashew apple was shown to be more strongly related to TEP and TG content. For the nutritional composition, the highest concentrations of Ca, Mg, P, Na and Fe were obtained in the coast; and the concentrations of N, K, Mn and Zn in the sertão region. It was concluded that the physical, the physical-chemical quality, the antioxidant activity of cashew apple and nutritional composition of cashew apple and leaves of dwarf cashew clones varies with region, year of production and genotype.